Enhancing Climate Information Services for Aquaculture at Scale: A decision support tool and potential platforms for managing climate risks in Bangladesh - Hossain, Peerzadi Rumana (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate information services for aquatic food systems are emerging as a relatively new field of research in climate smart development and gaining momentum on national, regional and international research platforms. In addition, aquatic food systems of Bangladesh, particularly aquaculture is highly momentous for livelihood, nutrition and food security particularly for the rural poor and vulnerable people. Contemporarily, the system is also confronting the hardest challenges of climate risks like sudden temperature fluctuations and flash floods. To manage the climate risks particularly temperature and rainfall variation in aquaculture operations, the study aims to explore how climate information can be translated in the form of advisory services. We used two-way communication to explore the understanding and level of resilience at end user level. We engaged information producers (i.e. the meteorological and aquaculture experts) and end users (i.e. the fish famers) and used explanatory methods i.e., key informant interview and focused group discussion for this purpose. We identified how temperature and rainfall forecasts can be contextually interpreted for fish farmers’ use. The identified advisories will help the fish farmers in making climate resilient decisions. We also did an analysis on potential platforms for effective transfer of the advisories to the fish farmers. It shows that public-private partnership development is crucial for enhancing climate information services at scale and for sustainability of the services after the project life span as well. In a nutshell, ensuring climate information services for aquatic foods in the food systems to manage climate risks, reduce loss and increase production is substantially important for building resilience and thus, to reach the broader goals of livelihood, food and nutrition security.